2018
DOI: 10.53627/jam.v5i2.3476
|View full text |Cite
|
Sign up to set email alerts
|

Respon Siswa Terhadap Media Dakon Matika Materi KPK dan FPB pada Siswa Kelas IV di SD/MI Lamongan

Abstract: This research aimed to know the response of the students against the media learning material on the matika dakon KPK and FPB in class IV. The research methods apply in this research is descriptive research. The subject of this research is 25 students of class IV SDN Tenggerejo 2 Kedungpring Lamongan. Research instrument used is a questionnaire form. The criteria of response consists of 5 indicators are judgments, interest, motivation, satisfaction, and response. The analysis of the questionnaire shows that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
1
7
0
10
Order By: Relevance
“…Because basically student learning activities are influenced by motivation. If students are motivated in learning activities, automatically students will be more interested in learning concepts that are abstract and will increase activity and learning outcomes [11]. It can be concluded that the tiktok application can motivate students in learning sciencebiology.…”
Section: Motivation To Learnmentioning
confidence: 99%
“…Because basically student learning activities are influenced by motivation. If students are motivated in learning activities, automatically students will be more interested in learning concepts that are abstract and will increase activity and learning outcomes [11]. It can be concluded that the tiktok application can motivate students in learning sciencebiology.…”
Section: Motivation To Learnmentioning
confidence: 99%
“…Respon adalah kesan atau tanggapan seseorang setelah melalui aktifitas penginderaan sehingga terbentuknya sikap positif atau sikap negatif (Khairiyah, 2018). Dengan kata lain respon adalah suatu tanggapan atau perasaan siswa setelah mengikuti pembelajaran.…”
Section: Pendahuluanunclassified
“…Respon adalah tanggapan atau rekasi yang timbul apabila terdapat objek yang menjadi bahan pengamatannya, sehingga memunculkan respon positif atau respon negatif (Khairiyah, 2019).…”
Section: Pendahuluanunclassified